Microbiome - Ravel, Jacques; Wellington, Elizabeth; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Microbiome: The scope of the journal encompasses studies of microbiomes colonizing humans, animals, plants or the environment, both built and natural or manipulated, as in agriculture. Studies on the development and application of meta-omics approaches or novel bioinformatics tools, on community/host interaction with emphasis on structure-function relationship that would lead to substantial advances in the field will be considered for publication. Microbiome is especially interested in studies that go beyond descriptive omics surveys and include experimental or theoretical approaches that mechanistically support proposed microbiome functions, and establish, if possible, cause and effect relationships. Studies of individual microbial isolates/species in vivo or in laboratory cultures without exploring the mechanisms by which they affect the complex microbiome structures and functions will not be considered. Through this collection of literature Microbiome hopes to integrate researchers with common scientific objectives across a broad cross-section of sub-disciplines within microbial ecology. Microbiome works closely with its sister journals Environmental Microbiome and Animal Microbiome, and with BMC Microbiology. If a submission is more appropriate for one of these journals, the opportunity to transfer the manuscript files to these journal will be offered. BEFORE YOU SUBMIT: Please read the Aims & Scope, our Editorial A blueprint for contempory studies of microbiomes, and the Submission Guidelines carefully, particularly in relation to Microbiome's data availability policies. Please note that the Journal does not consider unsolicited Reviews.
Keywords: Microbiology; Microbial genetics; Microbial populations; Microbial ecology; Veterinary microbiology; Medical microbiology; Microbiology; Microbial Genetics; Microbial Communities; Environmental Microbiology; Veterinary Microbiology; Medical Microbiology